Particle deposition and aggregation : measurement, modelling, and simulation - Elimelech, M. (Menachem) (Colloid and surface engineering series., 1995)
Particle Deposition and Aggregation: Measurement, Modelling and Simulation describes how particle deposition and aggregation can be measured, modeled, and simulated in a systematic manner. It brings together the necessary disciplines of colloid and surface chemistry, hydrodynamics, experimental methods, and computational methods to present a unified approach to this problem. The book is divided into four parts. Part I presents the theoretical principles governing deposition and aggregation phenomena, including a discussion of the forces that exist between particles and the hydrodynamic factor.